Selected Aspects Of Grounded Theory Methodology. A Qualitative Research Strategy - Barbara Skoczyńska-Prokopowicz (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Scientists conducting research in the field of social sciences are constantly looking for new ways of analysing the social reality. For many years, scientific research has successfully used quantitative methods alongside qualitative research methods. The grounded theory methodology is a type of methodology providing a basis for systematic empirical research and analysis of the obtained qualitative data. The presented article reviews the main points of the grounded theory. It also aims at comparing this methodology with an ethnomethodological approach and at indicating the role of the researcher in qualitative research.